2016
DOI: 10.3389/fpsyg.2016.01002
|View full text |Cite
|
Sign up to set email alerts
|

Cross-Validation of the Spanish HP-Version of the Jefferson Scale of Empathy Confirmed with Some Cross-Cultural Differences

Abstract: Context: Medical educators agree that empathy is essential for physicians' professionalism. The Health Professional Version of the Jefferson Scale of Empathy (JSE-HP) was developed in response to a need for a psychometrically sound instrument to measure empathy in the context of patient care. Although extensive support for its validity and reliability is available, the authors recognize the necessity to examine psychometrics of the JSE-HP in different socio-cultural contexts to assure the psychometric soundnes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
51
6
9

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 50 publications
(78 citation statements)
references
References 40 publications
(64 reference statements)
12
51
6
9
Order By: Relevance
“…These values are higher than the recommendation of the American Educational Research Association of 0.70, confirming the adequate psychometric reliability of all instruments used in a Spanish clinical context. These findings are also slightly superior to those previously reported for empathy ( Hojat et al, 2002 ; Alcorta-Garza et al, 2016 ), loneliness ( DiTommaso et al, 2004 ; Yárnoz Yaben, 2008 ), and collateral effects ( Blanch et al, 2010 ).…”
Section: Discussioncontrasting
confidence: 67%
See 1 more Smart Citation
“…These values are higher than the recommendation of the American Educational Research Association of 0.70, confirming the adequate psychometric reliability of all instruments used in a Spanish clinical context. These findings are also slightly superior to those previously reported for empathy ( Hojat et al, 2002 ; Alcorta-Garza et al, 2016 ), loneliness ( DiTommaso et al, 2004 ; Yárnoz Yaben, 2008 ), and collateral effects ( Blanch et al, 2010 ).…”
Section: Discussioncontrasting
confidence: 67%
“…To measure empathetic orientation in clinical encounters, the Jefferson Scale of Empathy (JSE; HP-Version) was used. The JSE includes 20 items that measure the empathetic behavior of physicians and other healthcare professionals in the context of patient care ( Hojat et al, 2002 ; Alcorta-Garza et al, 2016 ). The JSE is answered on a 7-point Likert scale (1 = strongly disagree, 7 = strongly agree), with higher scores associated with more empathetic behavior in the context of patient care.…”
Section: Methodsmentioning
confidence: 99%
“…The JSE includes 20 items that measure empathetic behavior of physicians and health professionals in the context of patients’ care (Hojat et al, 2002; Alcorta-Garza et al, 2016). The JSE is answered in a 7-point Likert scale (1 = strongly disagree, 7 = strongly agree).…”
Section: Methodsmentioning
confidence: 99%
“…In fact, there are no big differences among Latin American countries in terms of medical and nursing educational curricula (Andrade, 1978) and in public health policies (Atun et al, 2015). This is reflected in findings reported in Latin American physicians in relation to medical empathy (Alcorta-Garza et al, 2016), or attitudes toward inter-professional collaboration and lifelong learning (San Martín et al, 2016). In relation to professional roles and inter-professional relationships, two studies reported a “hierarchical” model as dominant in Mexican institutions (Hojat et al, 2001, 2003).…”
Section: Introductionmentioning
confidence: 98%
“…Both the theory related to context specificity and empirical studies indicate that constructs such as empathy should be viewed as locally construed global constructs. Finding out whether changes in empathy in medical school follow a discernible pattern or trend, or are indiscriminate across geographical boundaries would provide useful evidence as to how context specificity influences empathy.…”
Section: Introductionmentioning
confidence: 99%